What You Eat Matters: Nutrient Inputs Alter the Metabolism and Neuropeptide Expression in Egyptian Cotton Leaf Worm, Spodoptera littoralis (Lepidoptera: Noctuidae) - Doğan, Cansu; Güney, Gözde; Güzel, Kardelen K.; Can, Alp; Hegedus, Dwayne D.; Toprak, Umut (Frontiers in Physiology, 2021)
Lipids and carbohydrates are the two primary energy sources for both animals and insects. Energy homeostasis is under the strict control by the neuroendocrine system, and disruption of energy homeostasis leads to the development of various disorders, such as obesity, diabetes, fatty liver syndrome and cardiac dysfunction. One critical factor in this respect is feeding habbits and diet composition. Insects are good models to study the physiological and biochemical background of the effect of diet on energy homeostasis and related disorders; however, most studies are based on a single model species, Drosophila melanogaster. In the current study, we examined the effects of four different diets, high fat (HFD), high sugar (HSD), calcium-rich (CRD) and a plant-based (PBD) on energy homeostasis in younger (3rd instar) and older (5th instar) larvae of the Egyptian cotton leaf worm, Spodoptera littorolis (Lepidoptera: Noctuidae), in comparison to a regular artificial bean diet. Both HSD and HFD led to weight gain, while CRD had the opposite effect and PBD had no effect in 5th instar larvae and pupae. The pattern was the same for HSD and CRD in 3rd instar larvae, while a reduction in weight was detected with HFD and PBD. Larval development was shortest with the HSD, while HFD, CRD, and PBD led to retardation compared to the control. Trigylceride (TG) levels were higher with HFD, HSD, and PBD, with larger lipid droplet sizes, while CRD led to a reduction of TG levels and lipid droplet size. Trehalose levels were highest with HSD, while CRD led to a reduction at 3rd instar larvae, and HFD and PBD had no effect. Fifth instar larvae had similar levels of trehalose with all diets. There was no difference in the expression of the genes encoding neuropeptides SpoliAKH and SpoliILP1-2 with different diets in 3rd instar larvae, while all three genes were expressed primarily with HSD, and SpolisNPF was primarily expressed with HFD in 5th instar larvae. In summary, different diet treatments alter the development of insects, and energy and metabolic pathways through regulation of peptide hormones.